2015
DOI: 10.15517/rbt.v63i4.17866
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the environmental stress hypothesis for gall diversity of restinga vegetation on dunes

Abstract: Abstract:The Atlantic Coast Restinga is a mosaic of plant communities with a distinct floristic and phytophysiognomy, exposed to luminous, thermal, and saline stresses. Plants of the restinga must have special features commonly associated to xeric environments, and are expected to host a high diversity of galling herbivores. We studied gall morphotypes, and recorded the diversity of galls on plants growing in sand dunes in a remnant area of restinga (Acaraí State Park) in São Francisco do Sul, Santa Catarina S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
(48 reference statements)
0
11
0
3
Order By: Relevance
“…Surprisingly, stems were the organs most frequently affected by galling insects in Cordoba. This result disagrees with the general trend of leaves being the preferred organ for galling insects (Mani, 1964;Shorthouse & Rohfritsch, 1992;Quintero et al, 2014;Arriola et al, 2015;Kuzmanich et al, 2015;Maia & Carvalho-Fernandes, 2016). Just a few studies have reported a greater number of galls on plant stems (Fernandes et al, 2002;Veldtman & McGeoch, 2003;Carneiro et al, 2009;Coelho et al, 2013;), and in some of these cases, they were restricted to a single insect taxon, such as Coleoptera (Maia & Oliveira, 2004).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Surprisingly, stems were the organs most frequently affected by galling insects in Cordoba. This result disagrees with the general trend of leaves being the preferred organ for galling insects (Mani, 1964;Shorthouse & Rohfritsch, 1992;Quintero et al, 2014;Arriola et al, 2015;Kuzmanich et al, 2015;Maia & Carvalho-Fernandes, 2016). Just a few studies have reported a greater number of galls on plant stems (Fernandes et al, 2002;Veldtman & McGeoch, 2003;Carneiro et al, 2009;Coelho et al, 2013;), and in some of these cases, they were restricted to a single insect taxon, such as Coleoptera (Maia & Oliveira, 2004).…”
Section: Discussionmentioning
confidence: 78%
“…The plant families hosting the highest number of galls were Asteraceae (27.2 % of interactions) and Fabaceae (22.2 %). Several studies conducted in the Neotropical region reported Asteraceae (Carneiro et al, 2009;Coelho et al, 2013;Arriola et al, 2015;Kuzmanich et al, 2015) and Fabaceae (Fernandes et al, 2002;Coelho et al, 2009;Carvalho-Fernandes, Silva De Almeida-Cortez, & Ferreira, 2012;Urso-Guimarães et al, 2017) as the families most frequently attacked by galling insects. In Córdoba, the families best represented in the vegetation are Poaceae, Asteraceae and Fabaceae, in that order (Zuloaga, Morrone, & Rodriguez, 1999;Giorgis et al, 2011); the predominance of the last two plant families in our records is partially concordant with the "plant family size hypothesis", which predicts a positive correlation between the high number of plant species and the number of associated gall morphotypes (Fernandes, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…É sabido que em ambientes xéricos, ocorre uma alta diversidade e abundância de galhas (Fernandes & Price 1992;Price 1987), por isso, uma gama de estudos tem sido conduzida em vegetações sob condições xéricas, como cerrados, restingas e dosséis de florestas, com a finalidade de identificar as dinâmicas galhador-hospedeiro (Ribeiro & Basset 2007;Tuller et al 2013;Julião et al 2014;Arriola et al 2015;Arriola & Melo Jr. 2016;Silva et al 2016).…”
Section: Introductionunclassified
“…Em restinga, a maioria dos estudos sobre galhas consistem em levantamento e registro de espécies (Bregonci et al 2010;Maia 2013;Arriola et al 2015;Arriola & Melo Jr. 2016), sendo que poucos estudos avaliaram os fatores que afetam a dinâmica galha-hospedeiro. Em Dalbergia ecastophyllum (L.) Taubert.…”
Section: Introductionunclassified